Culturas de fin de siglo en América Latina - LUDMER, Josefina Compiladora (BEATRIZ VITERBO, 1994)
Contenido:ALONSO, Carlos; FRANCO, Jean; GONZALEZ, Anibal; GONZALEZ, Eduardo; GONZALEZ, Horacio; GONZALEZ ECHEVERRIA, Roberto; KRANIAUSKAS, John; MASIELLO, Francine; MOLLOY, Sylvia; MONSIVAIS, Carlos; MORENO, María; RAMOS, Julio; RICHARD, Nelly; ROWE, William; SALESSI, Jorge; SANTIAGO, Silviano; SCHWARZ, Roberto; SOMMER, Doris